Bioprospecting of Metarhizium rileyi (Ascomycota: Clavicipitaceae) without control of Spodoptera cosmioides (Walker) (Lepidoptera: Noctuidae) (Research, Society and Development, 2020)
The selection of entomopathogenic fungi strains is required choosing the most appropriate isolated to use in programs of biological pest control. The objective of the research was to evaluate, under laboratory conditions, the efficiency of isolated from entomopathogenic fungus Metarhizium rileyi on Spodoptera cosmioides. The experimental trial consisted of a completely randomized design with eight treatments and 10 repetitions with 5 caterpillars standardized in 2 mm each. Is was pulverized 1 mL of each strain in 1.0×109 viable conidia mL-1 with Potter tower assist. Mortality data obtained were transformed arcsen (x/100)0.5 to do the variance analysis and comparison of means by Scott-Knott test in 5% of significance. The efficiency of control was calculated through Abbot formula. The mortality was verified daily for 27 days and evaluated by linear regression and polynomial in such a way, M. rileyi was pathogenic to S. cosmioides caterpillars. The treatment with strain UFMS 03, UFMS 08 and UFMS 02 presented 89.5, 78.9, 73.7% of efficiency, respectively. Isolated UFMS 03 showed with median lethal time (LT50) in 14.7 days, higher efficiency with potential as a biological control agent.